Developing Novel Gas Discharge Emitters of Acoustic Waves in Air for Nondestructive Testing of Materials; Sensors; Vol. 22, iss. 23 - Derusova D. A. Dariya Aleksandrovna; Nekhoroshev V. O. Vitaly Olegovich; Shpilnoy V. Yu. Viktor Yurjevich; Vavilov V. P. Vladimir Platonovich (2022, 2022)
Title screen